Tumor-associated macrophages: Shifting bad prognosis to improved efficacy in cancer therapies? - Guillaume Harlé; Janske Nel; Camille Corbier; Nadège Touche; Stéphanie Grandemange (International Journal of Immunotherapy and Cancer Research - Peertechz Publications, 2021)
Macrophages are innate immune cells that play an important role in the response to damaged tissue and pathogenic infection. During activation, signals from the local environment induce macrophage polarization towards either the classical pro-inflammatory phenotype (M1) or towards the alternative anti-inflammatory phenotype (M2). In cancer, M2 tumor-associated macrophages (TAMs) are associated with a poor prognosis. Notably, the Tumor Microenvironment (TME) is known to promote the M2 phenotype by dampening anti-tumor immune responses and thus promoting tumoral growth. Recent studies have demonstrated that TAMs play a major role in cancer cells resistance to chemo- and radiotherapies leading to ineffective treatment strategies. This raises the importance of including macrophage targeting strategies, either to dampen their activities or to re-educate them toward pro-inflammatory phenotype, to improve the efficiency of current and future treatments. Therefore, this mini-review aims to highlight recent discoveries demonstrating how macrophages induce cancer resistance to therapies and how re-educated TAMs could be used to improve treatment outcomes.